Characterization of the microbocenosis in mountain soils of Dido-depression in the Republic of Dagestan - H. M. Gamzatova (Аграрная наука Евро-Северо-Востока, 2018)
The data about the soil cover of mountain Dagestan are scattered. A comprehensive assessment of the biological diversity of mountain soils by such indicators as the degree of humus content, the number and structure of the microbocenosis has not been carried out yet. This article provides the results of the analysis of the quantitative assessment of microbocenosis in mountain soils (Mollic Leptosols Eutric) of Dido-depression in the Republic of Dagestan. The investigations were carried out on the following types of soils differentiated according to altitude marks: Alpine meadow with the elements of steppe formation, Alpine brown weakly podzolized, Alpine meadow typical, Alpine brown podzolized, mountain-meadow subalpine, mountain-meadow alpine. The article describes the characteristic features of soil bacteria and fungi in their dependence on the altitude marks. A variety of soil bacteria and fungi has been identified according to their frequency and the abundance of morphological and cultural types. The minimum and maximum number of prokaryotes and micromycetes is shown and determined. This number varies depending on the site of soil samples selection. Based on the calculated frequency of occurrence there are identified dominant morphological and cultural types, subdominants, frequently occurring, rare, random. According to the Serensen coefficient, bacteriocenoses formed in soils up to a height of 1450 m are similar in their qualitative composition and structure. It has been established that with an increase in the height of the soil location, the number of prokaryotes decreases, and that of the micromycetes increases. The diversity of bacteria and fungi expands in soils which have the highest altitude. It is shown that in the soils located at an altitude of 1450m (the height of the first section), as well as at an altitude of 2350m (subalpine soil height) the bacteriocenosis similar in their quality composition are formed.